2017
DOI: 10.3389/fmed.2017.00086
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Global Disease Burden for the Optimization of Patient Management and Treatment

Abstract: BackgroundThe assessment and treatment of complex disorders is challenged by the multiple domains and instruments used to evaluate clinical outcome. With the large number of assessment tools typically used in complex disorders comes the challenge of obtaining an integrative view of disease status to further evaluate treatment outcome both at the individual level and at the group level. Radar plots appear as an attractive visual tool to display multivariate data on a two-dimensional graphical illustration. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
5
24
1
Order By: Relevance
“…However, it remains to be determined the consequence as well as the mechanisms involved in the increased accumulation of M2 macrophages in the CNS of parasite-infected Galectin-3 ÏȘ/ÏȘ mice. In this regard, it has been suggested that galectins, including galectin-3, can play a role in immune cell trafficking (Sperandio et al, 2009;Ge et al, 2013;Jia et al, 2013). However, our results showed that adoptively transferred galectin-3-sufficient as well as -deficient M2 macrophages accumulated in the CNS of both WT and Galectin-3 ÏȘ/ÏȘ mice with similar frequency.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, it remains to be determined the consequence as well as the mechanisms involved in the increased accumulation of M2 macrophages in the CNS of parasite-infected Galectin-3 ÏȘ/ÏȘ mice. In this regard, it has been suggested that galectins, including galectin-3, can play a role in immune cell trafficking (Sperandio et al, 2009;Ge et al, 2013;Jia et al, 2013). However, our results showed that adoptively transferred galectin-3-sufficient as well as -deficient M2 macrophages accumulated in the CNS of both WT and Galectin-3 ÏȘ/ÏȘ mice with similar frequency.…”
Section: Discussioncontrasting
confidence: 57%
“…Here we observed that the parasite-infected Galectin-3 ÏȘ/ÏȘ mice, despite showing the presence of an increased number of M2 macrophages in the CNS compared with their WT counterparts, exhibit severe neurological signs and are highly susceptible to the infection. In the CNS of Galectin-3 ÏȘ/ÏȘ mice, perhaps the observed elevated amount of the chemokines, including CCL2, which are known to involve in trafficking of monocytes/ macrophages (Ransohoff et al, 2003;Shi and Pamer, 2011), facilitates the increased influx of M2 cells. This indicated to us that the protective function, but not the development, of M2 cells is dependent on galectin-3.…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation studies, including influence on spouses, may help complement the present study; however, one should consider that different mechanisms of development of severe tinnitus may occur between men and women, as recently suggested. 13 …”
Section: Discussionmentioning
confidence: 99%
“…With tinnitus being a condition with highly unmet clinical needs ( Cederroth et al, 2013 ), the recent identification of a high heritability opens door to exciting research. Since it is more than likely that tinnitus is a polygenic trait and it will require the study of several thousand samples, audiologists and ENT doctors should optimize their phenotyping strategies for instance by using high frequency audiometry and multivariate questionnaire data ( Muller et al, 2016 ; Schlee et al, 2017 ), initiate incentives to allocate a specific ICD-code for bilateral tinnitus, and start biobanking samples ( Lopez-Escamez et al, 2016 ). Regarding the latter, since it is not custom for an ENT clinic to collect samples for DNA biobanking, guidelines should emerge to promote good practice ( Fuller et al, 2017 ) and enable the creation of a large consortium to join efforts to decipher the genetic basis of tinnitus.…”
Section: Perspectivementioning
confidence: 99%